PENGARUH MOTIVASI, KEMAMPUAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS SOSIAL KOTA SEMARANG - Rachmawati, Tyas Rizky; Widowati, Maduretno; Wahyuningsih, Susanti (STIE PENA, 2022)
This study aims to analyze the effect of motivation on employee performance, to analyze the effect of work ability on employee performance, to analyze the influence of the work environment on employee performance, to analyze the effect of motivation, work ability and work environment simultaneously on employee performance at the Semarang City Social Service. The population in this study were Civil Servants at the Semarang City Social Service, totaling 50 respondents. The sampling technique used in this study is the census method, where the entire population is used as a sample. The analytical tool used in this study is multiple linear regression analysis. The results of this analysis indicate that motivation has no effect on employee performance by proving that t.count 0.497 < t.table 1.67866, and a significance value of 0.622 > 0.05, work ability has a positive and significant effect on employee performance at the Social Service The city of Semarang. This can be shown by looking at the value in the t test analysis, it is known that the t.count value is 3.716 > t.table 1.67866, and the significance value is 0.01 <0.05, and the work environment influences employee performance with evidence that on the value of the t test analysis it is known that the t.count value is t.table the t.count value is 1.900 > 1.67866 t.table and the significance value is 0.064 > 0.05.Keywords: motivation, work ability, work environment, employee performanceThis study aims to analyze the effect of motivation on employee performance, to analyze the effect of work ability on employee performance, to analyze the influence of the work environment on employee performance, to analyze the effect of motivation, work ability and work environment simultaneously on employee performance at the Semarang City Social Service. The population in this study were Civil Servants at the Semarang City Social Service, totaling 50 respondents. The sampling technique used in this study is the census method, where the entire population is used as a sample. The analytical tool used in this study is multiple linear regression analysis. The results of this analysis indicate that motivation has no effect on employee performance by proving that t.count 0.497 < t.table 1.67866, and a significance value of 0.622 > 0.05, work ability has a positive and significant effect on employee performance at the Social Service The city of Semarang. This can be shown by looking at the value in the t test analysis, it is known that the t.count value is 3.716 > t.table 1.67866, and the significance value is 0.01 <0.05, and the work environment influences employee performance with evidence that on the value of the t test analysis it is known that the t.count value is t.table the t.count value is 1.900 > 1.67866 t.table and the significance value is 0.064 > 0.05. Keywords: motivation, work ability, work environment, employee performance